STATUS KEBERSIHAN GIGI DAN MULUT PADA NELAYAN DI KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO SULAWESI UTARA (e-GiGi, 2015)
Abstract: Oral hygiene is a part of the general health that is needed to be considered by the community. Some causes of a person neglecting his/her teeth and mouth cleanliness are level of education, level of knowledge, and the person's income. Generally, fishermen do not have enough time to take care of their oral hygiene. This study aimed to determine the status of oral hygiene of fishermen living in Bahu Malalayang Manado, North Sulawesi. This was a descriptive study using a cross sectional design. There were 63 fishermen, but only 38 fulfilled the inclusion and exclusion criteria. The results showed that based on the knowledge, most of the dental and oral hygiene status (62.52%) belonged to the medium category of OHI-S. Oral hygiene status Based on the characteristics of age, most of the age group of 36-45 years (61.29%) had the medium category of OHI-S. Distribution of oral hygiene status by education was most dominant subjects with secondary school education level that is equal to 81,82%. Distribution of oral hygiene status by income is most prevalent subject to income